Treatment of bauxite contaminated water at Sungai Pengorak using riverbank filtration system (RBF) - Tan, Yee Ling (2016)
Unregulated and rampant bauxite mining activities in Kuantan, Pahang have been seriously polluted the rivers and oceans nearby Sungai Pengorak and Pantai Pengorak. Commonly, surface water is treated by using conventional water treatment method that involved coagulation, filtration and disinfection process. Due to a higher cost in both construction and chemical usages like alum and chlorine in treating raw water for drinking purpose, therefore, in this study, a more economic and cost-effective alternative water treatment method has been implemented, namely riverbank filtration system (RBF). In this study, a fixed bed column test was conducted to evaluate the treatment efficiency of riverbank in Sungai Pengorak in treating bauxite contaminated water. The riverbank consists of mostly sand and some traces of seashells with a range of size from 7.000mm to 0.063mm. Malaysian Department of Environment Water Quality Index (DOE-WQI) were calculated and classified according to Interim National Water Quality Standards, Malaysia (INWQS). Water Quality Index (WQI) was determined on the basis of nine physico-chemical parameters like pH, colour, turbidity, dissolved oxygen (DO), total dissolved solids (TDS), total suspended solids (TSS), ammoniacal nitrogen (AN), biological oxygen demand (BOD) and chemical oxygen demand (COD). Results shown that, based on WQI and INWQS, the bauxite contaminated water in Sungai Pengorak is classified under Class IV and Class V (i.e. highly polluted) respectively. Data obtained from the WQI for raw water was 49.93. However, the bauxite contaminated water after column filtration test improved significantly to Class I (clean) and 95.65 with respect to WQI. In addition, results from the study also fulfilled the National Drinking Water Quality Standards (NDWQS). This study shown that the riverbank can be effectively and economically been used as a safe alternative to treat bauxite contaminated water.